Commercial Opportunities for Productive Development of the Quinoa: A Reflection from Food Security, Sovereignty and Justice - Cely Torres, Lucy Andrea; Ducón Salas, Julio Cesar; Lafosse, Hadrien (Cooperativismo & Desarrollo, 2017)
Purpose: Food security is one of the most pressing issues of our century because of its implications for the future. To that extent, this article is a preliminary attempt to shed light on the opportunities stemmingfrom the commercialization of quinoa. Description: We undertook this study to try and grasp why the Cosmovision of Andean populations consider quinoa as an alternative for development. We first go through some aspects of food security, sovereignty and justice, which will eventually lead us to take a closer look at quinoa’s proper characteristics and production process. We will complement our study by an analysis of data on the commercialization of quinoa in order to evaluate its opportunities internationally. Conclusions: Quinoa presents very interesting nutritive characteristics, offers a variety of seeds, is relatively easy to grow virtually anywhere and can be used in a number of byproducts. To that extent, it should be seriously considered as a palatable solution to the global food crisis.
Keywords: development; food; innovation; sovereignty; trade